Ischaemia with no obstructive coronary arteries: a review with focus on the Asian population - Rodney Yu-Hang Soh; Ting-Ting Low; Ching-Hui Sia; William Kok-Fai Kong; Tiong-Cheng Yeo; Poay-Huan Loh; Kian-Keong Poh (Singapore Medical Journal)
Ischaemia with no obstructive coronary arteries (INOCA) has been a diagnostic and therapeutic challenge for decades. Several studies have demonstrated that INOCA is associated with an increased risk of death, adverse cardiovascular events, poor quality of life and high healthcare cost. Although there is increasing recognition of this entity in the Western population, in the Asian population, INOCA remains elusive and its prevalence uncertain. Despite its prognostic significance, diagnosis of INOCA is often delayed. In this review, we identified the multiple barriers to its diagnosis and management, and proposed strategies to overcome them.